Physico-Chemical Characteristics and antioxidant Activity of Phenolic Compounds and oil of Citrus aurantium Seeds from Northwest Algeria - Brixi Nassima Gormat; Meriem BELARBI; Zoubida MAMI; Fatima Zohra DJAZIRI (International Journal of Phytomedicine, 2015)
Sour orange (Citrus aurantium) is a tree of the family of Rutaceae. It is cultivated today in many parts of the world; the fruit, leaves, twigs and flowers have numerous applications in food and perfumery. Citrus aurantium used in this study originate from Tlemcen in North East of Algeria. Our study focused firstly on the physicochemical analysis of seed oil of sour orange namely the determination of indices, fatty acids, vitamin E and polyphenols. Secondly we evaluated total phenols, flavonoids, condensed tannins of Citrus aurantium seeds and their antioxidant activity of using in vitro methods: ferric reducing antioxidant power (FRAP) assay and β-carotene bleaching test. The seeds oil contents is 38.21%, their fatty major acids were palmitic (26.85 %) and linoleic acid (38.29%). The physicochemical analysis of oil showed index values of density, acid value, ester value, saponification value and refractive index estimated respectively: 0926; 1.212, 190.39, 191.52, 1467. The quantitative estimation of Citrus aurantium seeds showed that content of polyphenol is 2.12 mg GA /g DW which the predominant part is represented by tannins (0.3 mg CE /g DW) followed by the flavonoids (0.076 mg CE /g DW). Our results demonstrate that all extracts have antioxidant capacity. Among these extracts, the ethyl acetate fraction of flavonoids showed the highest value of antioxidant activities for seed which might constitute an important source of natural antioxidants.